2021
DOI: 10.3390/agriculture11060508
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emitter Structure on Its Hydraulic Performance Based on the Vortex

Abstract: The rectangular labyrinth emitter is taken as the study object in this article, as we added internal teeth to vortex-free and vortex areas in its lateral channel or lengthened the vertical channel, to change the channel structure. Using the computational fluid dynamics (CFD) method simulates the water flow field, to get the relationship between flow rate and pressure, and the vortexes distribution in channel. The aim of this study is to explore the reasons for the influence of structural change on hydraulic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The average error was less than 3%, and the correlation coefficient was higher than 0.9. The simulated flow rate was greater than the measured flow rate, which is consistent with the findings of Xu and Zhang (2020) and Wang et al (2021). The possible reason is that the smoothness of the walls cannot be guaranteed during the test model processing, which leads to additional energy dissipation in the leaf vein flow channel, and another possible reason is that a suitable turbulence model was not selected during the simulation.…”
Section: Discussionsupporting
confidence: 91%
“…The average error was less than 3%, and the correlation coefficient was higher than 0.9. The simulated flow rate was greater than the measured flow rate, which is consistent with the findings of Xu and Zhang (2020) and Wang et al (2021). The possible reason is that the smoothness of the walls cannot be guaranteed during the test model processing, which leads to additional energy dissipation in the leaf vein flow channel, and another possible reason is that a suitable turbulence model was not selected during the simulation.…”
Section: Discussionsupporting
confidence: 91%
“…Increasing the fluid velocity and turbulence inside the emitters can contribute to improved anti-clogging performance. Computational Fluid Dynamics (CFD)-based numerical simulation techniques have been widely applied in the design and development of emitters, playing a significant role in optimizing channel design and enhancing anti-clogging capabilities [76]. Pipeline damage can result from multiple factors: aging of the pipeline material, breakage caused by expansion and contraction under varying temperatures, damage inflicted by plowing equipment, and damage from rodents [20].…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that increasing the flow velocity as well as increasing the labyrinth channel dimensions could reduce sediment accumulation and improve the performance of the irrigation system. The high turbulence present in the labyrinths creates vortices that serve as essential mechanisms for controlling fluid discharge and dissipating energy (Wang et al, 2021;Wei et al, 2006).…”
Section: Flow Characterization: Mean Velocity and Streamlinementioning
confidence: 99%